CD8+CXCR5+ T Cells Regulate Pathology in the Genital Tract - Janina Jiang; Cheryl I. Champion; Bo Wei; Guangchao Liu; Kathleen A. Kelly (Hindawi Limited, 2013)
We have identified a CD8+CXCR5+ T cell that prevents the development of oviduct dilation following C. muridarum genital infection. Phenotypic studies show that CD8+CXCR5+ cells express markers of T regulatory cells (FoxP3, CD25, and GITR) but do not express a necessary component of cytotoxic cells (perforin). Cxcr5-/- mice have significantly lower numbers of CD8+ cells and lack the CD8+CXCR5+ population while the total number of CD4+ cells is equivalent between mouse strains. The transfer of CD8+ splenocytes from WT mice reduces the oviduct dilation seen in Cxcr5-/- mice following C. muridarum infection. Future studies will investigate the mechanism by which this cell type regulates genital tract pathology.